2018
DOI: 10.1039/c7nr09396a
|View full text |Cite
|
Sign up to set email alerts
|

Balancing silicon/aluminum oxide junctions for super-plasmonic emission enhancement of quantum dots via plasmonic metafilms

Abstract: We study the impact of structural features of Si/Al oxide junctions on metal-oxide plasmonic metafilms formed via placing such junctions in close vicinity of an Au/Si Schottky barrier. The emission intensity and dynamics of colloidal semiconductor quantum dots deposited on such metafilms are investigated, while the surface morphology and structural compositions of the Si/Al oxide junction are controlled. The results show the conditions wherein the Si/Al oxide junction can reshape the impact of plasmonic effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 47 publications
1
22
0
Order By: Relevance
“…In fact, because SiO 2 has a very large bandgap (Figure a), it prevents migration of photoexcited electrons from QDs to defect sites in the substrate, leading to higher emission and longer lifetimes (Figure a, line 2). Additionally, our previous reports have shown that when QDs are spin coated on an ultrathin layer of Al oxide (0.5–1 nm) deposited on the top of a Si layer, they can become brighter with longer lifetimes. ,, This is due to the surface charges formed at the Si/Al oxide interface . In the cases studied here, however, the Al oxide layers were deposited on the glass substrate, introducing some defects, instead.…”
Section: Photocatalytic Design Of the Defect Environment Of Quantum Dotsmentioning
confidence: 94%
See 1 more Smart Citation
“…In fact, because SiO 2 has a very large bandgap (Figure a), it prevents migration of photoexcited electrons from QDs to defect sites in the substrate, leading to higher emission and longer lifetimes (Figure a, line 2). Additionally, our previous reports have shown that when QDs are spin coated on an ultrathin layer of Al oxide (0.5–1 nm) deposited on the top of a Si layer, they can become brighter with longer lifetimes. ,, This is due to the surface charges formed at the Si/Al oxide interface . In the cases studied here, however, the Al oxide layers were deposited on the glass substrate, introducing some defects, instead.…”
Section: Photocatalytic Design Of the Defect Environment Of Quantum Dotsmentioning
confidence: 94%
“…In the presence of a large number of defect sites (small quantum yields), one can expect large P enh values, while under the same plasmonic settings when the defect sites are suppressed, these factors become smaller. Recently, we showed one can use plasmonic effects not only to enhance the near fields experienced by QDs but also to suppress their DEs. This makes QDs unique superemitters by increasing their quantum yields by both the Purcell effect and the quarantine of their excitons against the substrate and surface defect sites.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous results have shown such a thickness is optimized for generation of grains of Al oxides and effective Si/Al oxide charge barriers. [ 23 ] After this, solutions of CdSe/ZnS and PbS QDs or their mixtures with equal volume ratios (CdSe + PbS) were spin‐coated on the top of the Al oxide layers. The QDs were acquired from NN‐Labs, LLC.…”
Section: Methodsmentioning
confidence: 99%
“…The 1 nm of Al on the Si layer forms gains of Al oxides. [ 23 ] Such grains are expected to support large bandgaps (Figure 11a) and negative charge densities formed at few nanometers away from the Si/Al oxide interface inside the Al oxide region. [ 50–53 ] Considering such a charge barrier, for the case of CdSe/ZnS QDs the stronger emission enhancement seen in Figure 7a can be associated with the more efficient hot electron excitations in the Ag/Si junction.…”
Section: Field‐effect Passivation Via Entrapment Of Hot Electrons In mentioning
confidence: 99%
See 1 more Smart Citation